Performance of broiler fed on diet containing Koroch (Pongamia pinnata) seed cake - Husna, AU; Habib, M; Islam, MT; Ferdaus, AJM; Ali, MS (Bangladesh Journal of Animal Science, 2017)
A total of 180 day old broiler chicks (Cobb 500) were allocated randomly to five treatment groups with 3 replicate having 12 birds in each reared for a period of 28 days. The aim of this study was to find out whether koroch seed cake (KSC) had any effect upon broiler at different age group. Therefore, two diets were formulated: 1) basal diet with 0% KSC and 2) basal diet with 2% KSC. The birds of different treatment groups received either diet i or ii in the following way: Control group (T1)=0% KSC throughout the experimental period, T2 =1st 21days 0% KSC diet + rest 7 days 2% KSC diet, T3=1st 14days 0% KSC diet + rest 14 days 2% KSC diet, T4=1st 7 days 0% KSC diet + rest 21 days 2% KSC diet, and T5=2% KSC throughout the experimental period. Body weight, body weight gain, feed consumption and mortality of broilers were recorded weekly and also whole experimental period. Feed conversion ratio (FCR) was also calculated. Weekly body weight and body weight gain did not show significant differences during 1st, 2nd and 4th week of age, while significant differences were found in 3rd week of age. In 3rd week, the body weight and body weight gain was the lowest in T5 (fed 2% KSC diet) among the Treatments. The final body weight was 906.69, 864.05, 869.92, 860.87 and 838.89 g for T1, T2, T3, T4 and T5, respectively and found non-significant result. Similar pattern of result found in body weight gain of the birds. Feed intake and feed conversion ratio of birds at different weeks and during whole experimental period did not differ significantly (p>0.05). All the meat yield parameters showed a non-significant effect of age of broilers fed with 2% KSC. Results of this experiment revealed that the feeding of 2% KSC at different ages fail to show any significant effect on broiler performance. Bang. J. Anim. Sci. 2017. 46 (2): 88-94